тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртрр тртртртртртрртиртитртррг тртртртртртрртиртитртрр
ответ:1) х=[(4/3)-у]
х=[(4/3)-у]
х=[(4/3)-1]
х=[(4-1×3)/3]
х=1/3
3х-2у=-1
3×[(4/3)-у]-2у=-1
4-3у-2у=-1
-5у=-1-4
-5у=-5|÷(-5)
у=1
ответ: ((1/3);1).
2) х=-2(1/6)+2у
х=2у-(13/6)
х=[((2×6)у-13)/6]
х=[(12у-13)/6]
х=[(12×1-13)/6]
х=[(12-13)/6]
х=(-1/6)
5х+у=(1/6)|×6
30х+6у=1
30×[(12у-13)/6]+6у=1
5×(12у-13)+6у=1
60у-65+6у=1
66у=1+65
66у=66|÷66
у=1
ответ: ((-1/6);1).
3) у=(-1-2х)
у=(-1-2×(13/28))
у=-1-(13/14)
у=(-1×14-13)/14
у=(-14-13)/14
у=-(27/14)
5х-4(-1-2х)=10,5
5х+4+8х=10,5
14х=10,5-4
14х=6,5|÷14
х=6,5/14
х=(65/10×14)
х=(13×5)/(2×5×14)
х=(13/28)
ответ: ((13/28);(-27/14)).
х= 2.72